PENERAPAN METODE TIME-DRIVEN ACTIVITY-BASED COSTING UNTUK MENGHITUNG HARGA POKOK PRODUK JASA: STUDI KASUS SALON KECANTIKAN AVV MAKE UP & HAIR DO - Devina, Marceline; Faliany, L. Jade (Jurnal Akuntansi, 2016)
Calculating costs of production is important but complex in its implementation, specifically with respect to the allocation of indirect costs to costs of production. There are several methods to calculate costs of production. In this study, the Time-Driven Activity Based Costing (TDABC) method was applied to calculate costs of production ofAVV Make Up & Hair Do, a beauty salon located at ITC BSD. The analysis showed that the TDABC was a suitable method for the beauty salon because it helped calculate the base price of each of its products and services.